Keynesian Theory and the AD-AS Framework: A Reconsideration - Amitava K. Dutt; Peter Skott (University of Massachusetts, Department of Economics, 2005)
Contrary to what has been argued by a number of critics, the AD-AS framework is both internally consistent and in conformity with Keyness own analysis. Moreover, the eclectic approach to behavioral foundations allows models in this tradition to take into account aggregation problems as well as evidence from behavioral economics. Unencumbered by the straightjacket of optimizing microfoundations, the approach can provide a useful starting point for the analysis of dynamic macroeconomic interactions. In developing this analysis, the AD-AS approach can draw on insights from the Post Keynesian, neo-Marxian and structuralist traditions, as well as from the burgeoning literature on behavioral economics. JEL Categories: E12, O11, B22, B41, B50
Keywords: 330; AS-AD; Keynes; New Keynesian theory; microeconomic foundations